Language Readability Levels of Reading Passages and Comprehension Levels of Exercises in Scaffolding English Coursebooks - Listianingsih, Lusiana; Harjanto, Ignatius (ANIMA Indonesian Psychological Journal, 2013)
Reading passages should have language readability levels suiting to students’ grade levels. Indeed, reading comprehension exercises should help students develop their competences in comprehending texts. This study investigated the language readability levels of reading passages and the comprehension levels of exercises in Scaffolding for Grades 7, 8, and 9. Assessed using Flesch-Kincaid formula and Fry figure, the language readability levels of reading passages in Scaffolding coursebooks were below the grade levels of Indonesia EFL students using the coursebooks. Judged using Barrett’s Reading Comprehension Taxonomy, exercises in Scaffolding coursebooks were dominated by literal comprehension and reorganization exercises, and supplemented with low numbers of inferential comprehension and evaluation exercises. Bacaan dalam buku teks seharusnya mengandung bahasa (kata dan kalimat) yang dapat di- mengerti siswa yang menggunakannya. Latihan yang menyertai bacaan juga seharusnya mengembangkan kemampuan siswa untuk memahami bacaan. Penelitian ini mengevaluasi tingkat keterpahaman bahasa dalam bacaan pada buku teks bahasa Inggris Scaffolding oleh siswa, dan seberapa besar latihan yang menyertai bacaan membantu pemahaman bacaan oleh siswa. Hasil evaluasi keterpahaman bahasa dalam bacaan menggunakan formula Flesch-Kincaid dan Fry menunjukkan bahwa bahasa yang digunakan dalam bacaan di bawah tingkat siswa yang menggunakan buku teks tersebut. Hasil evaluasi latihan bacaan menggunakan Taksonomi Barrett menunjukkan bahwa sebagian besar latihan mengembangkan pemahaman literal dan reorganisasi, dengan sebagian kecil latihan mengembangkan pemahaman inferensial dan evaluasi.